Their all-star summer - Newell, Kaylie (Newell, Kaylie. Sisters of Christmas Bay., 2023)
Marley Carmichael looks forward to a fresh start as the new voice for Christmas Bay's minor league baseball team, the Tiger Sharks, never expecting to begin a relationship with Sharks' pitcher Owen Taylor or to be faced with an unexpected pregnancy.